Unusual intrauterine retained fetal skeletal bony fragments: A case report and review of the literature. Issue 4 (19th April 2023) - Mremi, Alex; Mwidibo, Yusuph; Mlay, Joseph; Mchome, Bariki
Abstract: An unusual finding in hysterectomy specimen. Associated with a history of abortion. Etiology remains unclear. Clinically it presents with infertility, chronic pelvic pain, menorrhagia, and vaginal discharge. Treatment is by hysterescopic excision. Abstract :